(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Preventive maintenance (PM) is a critical aspect of ensuring the reliability and safety of biomedical equipment in healthcare settings. This article explores the significance of PM for nurses and provides practical tips for its implementation. Beginning with an overview of PM’s role in healthcare, it delineates key components including regular inspections, scheduled servicing, and documentation. Nurses play a pivotal role in advocating for and executing PM protocols to safeguard patient well-being. Challenges such as time constraints and resource limitations are addressed, alongside solutions to foster effective PM practices. Real-world case studies underscore successful PM program implementations. This article aims to empower nurses with the knowledge and skills necessary to prioritize PM and uphold patient safety.